2007
DOI: 10.1016/j.virol.2006.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Molecular features of new Peach Latent Mosaic Viroid variants suggest that recombination may have contributed to the evolution of this infectious RNA

Abstract: Nucleotide sequences of a broad range of Peach Latent Mosaic Viroid (PLMVd) variants were determined. The variants were isolated from peach, pear, and almond tree samples collected in Tunisia. Sequence analysis confirmed the high variability of PLMVd, as no less than 119 new variants were identified. Variations included new polymorphic positions, insertions of 11 to 14 nucleotides, and new mutations within the hammerhead self-cleavage motifs. We provide the first covariation-based evidence for certain stems wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 28 publications
3
11
0
1
Order By: Relevance
“…More specifically, a dimeric head-to-tail transcript of the PLMVd.282 variant (accession number: DQ680690), which is referred to as the “parental sequence” in this report, was used to infect a GF-305 indicator cultivar peach tree. This 337-long variant, which we identified in a previous sequencing study [16], bears one additional adenosine between nucleotides 107 and 108. It was shown to be infectious when inoculated into the GF-305 cultivar over the course of inoculation experiments performed with several other PLMVd variants (data not shown).…”
Section: Resultsmentioning
confidence: 58%
“…More specifically, a dimeric head-to-tail transcript of the PLMVd.282 variant (accession number: DQ680690), which is referred to as the “parental sequence” in this report, was used to infect a GF-305 indicator cultivar peach tree. This 337-long variant, which we identified in a previous sequencing study [16], bears one additional adenosine between nucleotides 107 and 108. It was shown to be infectious when inoculated into the GF-305 cultivar over the course of inoculation experiments performed with several other PLMVd variants (data not shown).…”
Section: Resultsmentioning
confidence: 58%
“…The PLMVd variants described in this work were highly homologous (97-100%) to the previously reported PLMVd, isolated from Tunisian peach, pear and almond trees clustered in group II (subgroups IIA and IIB) by Hassen et al (2007). These variant sequences are characterised by seven informative polymorphisms (U17, A24, A/U 42, A178, U 185, U/A 299 and A321), maintained in Czech PLMVd isolates, except for two variations (C17 and G24) in the DX2 isolate.…”
supporting
confidence: 71%
“…Even if ASBVd, the type member of this family, was initially proposed to fold into an elongated conformation (Symons, 1981), other data point to a bifurcated left-terminal domain (Gast et al, 1996; Navarro and Flores, 2000). Moreover, molecular characterization of Peach latent mosaic viroid (PLMVd; Hernández and Flores, 1992), and Chrysanthemum chlorotic mottle viroid (CChMVd; Navarro and Flores, 1997) predicted multibranched most stable conformations, and subsequent sequencing of many natural variants of PLMVd (Ambrós et al, 1998, 1999; Pelchat et al, 2000; Malfitano et al, 2003; Rodio et al, 2006; Fekih Hassen et al, 2007; Yazarlou et al, 2012), and CChMVd (De la Peña et al, 1999; De la Peña and Flores, 2002) not only corroborated this view, but also provided evidence for the significance of the multibranched conformations in vivo . Additional credence for such a PLMVd secondary structure was obtained by in vitro nuclease mapping and oligonucleotide binding shift assays (Bussière et al, 2000); this work also indicated the existence of an element of tertiary structure, specifically a pseudoknot interaction between two hairpin loops stabilizing the proposed branched conformation (see below), and suggested the possibility of a similar kissing-loop interaction in CChMVd (Bussière et al, 2000).…”
Section: Rod-like Versus Branched Secondary Structure: In Silico and mentioning
confidence: 99%
“…Evidence for the physiological relevance of the branched conformations proposed for PLMVd and CChMVd is particularly strong. Sequencing of many natural variants has shown that they display an extreme sequence heterogeneity (Ambrós et al, 1998, 1999; De la Peña et al, 1999; Pelchat et al, 2000; De la Peña and Flores, 2002; Malfitano et al, 2003; Rodio et al, 2006; Fekih Hassen et al, 2007; Yazarlou et al, 2012), most likely resulting from the high mutation rate of these viroids during replication catalyzed by a single-subunit, nuclear-encoded chloroplastic RNA polymerase without proof-reading ability (Navarro et al, 2000; Rodio et al, 2007); this mutation rate has been measured for CChMVd and is the highest reported for any biological entity (Gago et al, 2009). Remarkably, however, the sequence heterogeneity occurs in such a manner that the changes map at loops or, when affecting a base-pair, they are mostly co-variations or substitutions of Watson–Crick by wobble base-pairs (or vice-versa) that do not distort the computer-predicted branched conformations.…”
Section: Rod-like Versus Branched Secondary Structure: In Vivo Evidencementioning
confidence: 99%